2023
DOI: 10.29333/iji.2023.16245a
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Preference of Grammar Learning Model Amid Covid-19 Pandemic: A Mixed-Methods Study

Abstract: Covid-19 Pandemic has greatly affected EFL learners in English grammar. Learning English grammar in its nature is difficult for EFL learners. Covid-19 has made grammar lessons more difficult for them and has caused them to be differentiated sharply in their preference of learning model. Thus, this study is aimed at investigating the underlying factors causing the learners' differentiation of learning model in learning English grammar. Through a mixed-methods, using google-form that consists of closed and open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Indeed, learner engagement has long been characterized as "one of the hottest research topics in the eld of educational psychology" (Sinatra, et al, 2015, p. 1). This interest is evident from a number of publications on educational psychology, where mixed theoretical and practical aspects of engagement, especially in the eld of language learning (e.g., Hendriani et al, 2023;Hiver, et al, 2021;Mercer & Dornyei, 2020) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, learner engagement has long been characterized as "one of the hottest research topics in the eld of educational psychology" (Sinatra, et al, 2015, p. 1). This interest is evident from a number of publications on educational psychology, where mixed theoretical and practical aspects of engagement, especially in the eld of language learning (e.g., Hendriani et al, 2023;Hiver, et al, 2021;Mercer & Dornyei, 2020) have been reported.…”
Section: Introductionmentioning
confidence: 99%